Marginal Paris : Representing the Shadows of the City of Light - Salmon, Carole; Wiele, Aurélie Van de (Francopolyphonies, 2025)
This volume invites you to wander through the shadows of the City of Light and discover another, often invisible and silent Paris. Its chapters explore Parisian margins, including various populations, spaces and practices, as represented in French literature and cinema since 1800. You will take a peek at the Parisians' criminal activities and nocturnal lives in the nineteenth century, and witness how industrialization and capitalism between the 1850s and the 1970s reshaped the socioeconomic map of the city by creating or reinforcing spaces of social inequity. You will also meet marginalized groups that are often ignored or neglected in today's Paris-and French society-including the LGBTQIA+, Black and immigrant communities.